Minor allele C of rs12807809 polymorphism in NRGN contributes to the severity of psychosis in patients with Schizophrenia in South Indian population. (10th May 2017) - Sudesh, Ravi; Priyadarshini, Thirunavukkarasu; Preeti, Rajendran; John, Sujit; Thara, Rangaswamy; Mowry, Bryan; Munirajan, Arasamabattu Kannan
Highlights: The SNP rs12807809 in NRGN is a promising risk variant identified for schizophrenia by genome-wide association studies. We investigated the association of NRGN rs12807809 in 1005 Schizophrenia patients and 1069 controls in South Indian population. The rs12807809 in NRGN showed a significant difference between cases and controls and is associated with Schizophrenia. The minor non-risk allele 'C' contributes to the severity of psychosis in this study population. Abstract: Schizophrenia (SCZ) as a severe and complex neuropsychiatric disorder and is characterized by positive symptoms, negative symptoms and cognitive dysfunctions. Genome-wide association studies (GWAS) have identified a strong association between the single nucleotide polymorphism (SNP) rs12807809 upstream of Neurogranin ( NRGN) in a European population. This evidence prompted us to conduct an association study among 1005 schizophrenia cases and 1069 controls in a South Indian Population using TaqMan Allelic discrimination method. We observed an association of rs12807809 with SCZ in this study population. Allele frequencies and genotype frequencies of rs12807809 showed significant differences between cases and control subjects [p = 0.0019 ; OR = 0.69; 95% CI = (0.55–0.87)] and(p = 0.0062) . Further Genotype-Phenotype correlation revealed a moderate association of rs12807809 with flat affect (p = 0.039 ) and Hallucinations (p = 0.012 ). The ancestral non-risk C allele contributes to the severity of psychosis (p = 0.039 ) in this population.